ENT, head and neck diseases made easy - Anand, V. (Jaypee Brothers Medical Publishers (P) Ltd., 2011)
Practical, step by step guide through evolution and treatment of ENT, head and neck diseases. Includes DVD of radiological pictures to assist learning.